The Concept of Harmony in Javanese Society - Sri Lestari; Fatturochman; Goretti Adiyanti; Bimo Walgito (Faculty of Psychology, Universitas Surabaya, 2013)
Harmony is an important value that guides the behavior of Javanese. The purpose of this study is to explore the meaning of harmony for Javanese. Data were collected through in depth interviews of 12 participants, consisting of four fathers, four mothers, and four teenagers from Surakarta. Harmony is identified as maintaining connections, compatibility, resolving conflicts peacefully and empathy. Harmony consists of two categories, pseudo-harmony and essential harmony. Pseudo-harmony is maintaining relationship by burying conflicts. Essential harmony is maintaining harmony in togetherness with empathy toward each other. The implication of this study on the realm of education is discussed. Rukun merupakan salah satu nilai penting yang memandu perilaku orang Jawa. Studi ini bertujuan mengeksplorasi makna rukun bagi orang Jawa. Data diperoleh melalui wawancara mendalam pada 12 partisipan, terdiri atas empat ayah, empat ibu, dan empat remaja yang berasal dari Surakarta. Rukun dicirikan dengan menjaga keterhubungan, menjaga keselarasan, serta mengelola konflik dan bersikap peduli. Rukun mewujud dalam dua kategori yakni rukun semu dan rukun esensial. Rukun semu berarti menjaga keterhubungan dengan memendam konflik. Rukun esensial adalah menjaga harmoni dalam kebersamaan disertai sikap saling peduli. Didiskusikan implikasi hasil penelitian pada dunia pendidikan.